2017
DOI: 10.1038/ja.2017.74
|View full text |Cite|
|
Sign up to set email alerts
|

Allantopyrone A interferes with multiple components of the TNF receptor 1 complex and blocks RIP1 modifications in the TNF-α-induced signaling pathway

Abstract: Allantopyrone A is a fungal metabolite that uniquely possesses two α,β-unsaturated carbonyl moieties. We recently reported that allantopyrone A inhibited the nuclear factor-κB (NF-κB) signaling pathway induced by tumor necrosis factor (TNF)-α in human lung carcinoma A549 cells. In the present study, the mechanism by which allantopyrone A inhibits the TNF-α-induced signaling pathway was investigated in more detail. Allantopyrone A blocked extensive modifications to receptor-interacting protein 1 (RIP1) in the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…We previously reported that allantopyrone A, possessing two α,β-unsaturated carbonyl moieties, binds and crosslinks multiple proteins, including TNF-R1, which blocks the TNF-α-induced NF-κB pathway [47]. Allantopyrone A directly bound to TNF-R1 because it reduced the reactivity of the anti-TNF-R1 antibody to an epitope containing a cysteine residue in the extracellular CRD [47]. Western blotting using different antibodies recognizing TNF-R1 excluded the possibility that cucurbitacin B bound to TNF-R1 in a similar manner to allantopyrone A.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that allantopyrone A, possessing two α,β-unsaturated carbonyl moieties, binds and crosslinks multiple proteins, including TNF-R1, which blocks the TNF-α-induced NF-κB pathway [47]. Allantopyrone A directly bound to TNF-R1 because it reduced the reactivity of the anti-TNF-R1 antibody to an epitope containing a cysteine residue in the extracellular CRD [47]. Western blotting using different antibodies recognizing TNF-R1 excluded the possibility that cucurbitacin B bound to TNF-R1 in a similar manner to allantopyrone A.…”
Section: Discussionmentioning
confidence: 99%
“…A pCR3 expression vector encoding C-terminal FLAG-tagged human TNF-R1 was previously described [47]. A pGL4.22[luc2CP/Puro] vector containing the ICAM-1 promoter (−1604 to +40) was previously described [55].…”
Section: Plasmidsmentioning
confidence: 99%
“…The pCR3 expression vector encoding C-terminal FLAG-tagged human full-length TNF-R1 was previously described [42]. A549 cells were transfected with the pCR3 expression vector encoding TNF-R1-FLAG by the lipofection method using HilyMax transfection reagent (Dojindo, Kumamoto, Japan).…”
Section: Transfectionmentioning
confidence: 99%
“…Allantopyrone A is a natural metabolite produced by the endophytic fungus Allantophomopsis lycopodiana KS-97 and contains two α,β-unsaturated carbonyl moieties [44], which are reactive to cysteinyl thiol groups. We previously showed that allantopyrone A, which directly bound to TNF-R1, possibly via cysteine residues, reduced the TNF-R1 reactivity of H-5, which appeared to decrease TNF-R1 bands on Western blots [42]. To exclude this possibility, we transfected A549 cells with an expression vector encoding C-terminal FLAG-tagged TNF-R1.…”
Section: Isopanduratin a Decreased The Expression Of Tnf-r1mentioning
confidence: 99%
See 1 more Smart Citation